A survey on the fire safety awareness in residential collegues in UiTM : Kolej Mawar, Kolej Melati and Kolej Anggerik / Norain Eman - Eman, Norain (Faculty of Architecture, Planning and Surveying, 2013)
Fire safety aspect is the important element in every building. The aspect of fire in every building is different. This research is about a survey on the fire safety awareness in residential collegues in UITM Shah Alam. Some of the students that stay at residential Collegues did not aware about the fire safety equipment in the building. The research carries out through the distribution of the questionnaire and the interview sessions with the respondent that responsible for the facilities management for every building in UITM Shah Alam. Most of them have the basic knowledge of the fire safety equipment. But, they did not know the function of the fire safety aspect except as a fire protection. The study carries out at Kolej Mawar, Kolej Melati and Kolej Anggerik. Through the observation, the selection of the fire equipment that provided in the building is based on the environment of the building. Since the building is a residential colleagues the sprinkler is not provided in the building. All of these residential collegues has almost the same fire equipment. The result of the study is to recommend the best practice to improve awareness among students in the residential collegues.